P13 Clinical, radiographic and pulmonary function findings in silicosis. (16th November 2010) - Lucas, CD; Hirani, N; Simpson, AJ; Reid, PT
Abstract : Introduction: Silicosis is a pneumoconiosis caused by the inhalation of respirable silica. The condition is irreversible, and may be complicated by other pulmonary and non-pulmonary diseases. We describe clinical, radiographic and pulmonary function testing characteristics in a case series of silicosis. Methods: Cases were identified from clinics in two Edinburgh teaching hospitals. The diagnosis was based on characteristic radiographic features and a history of exposure to respirable silica; in two subjects silicosis was confirmed by surgical biopsy. Average length of follow up was 64 months. Results: 18 cases were identified, all were male. Median age = 52 years (range 28–66). 12 subjects worked as stonemasons, 5 as miners and 1 in a brick works. Common symptoms at presentation were dyspnoea (61%), cough (44%) and sputum (33%) but one-third were entirely asymptomatic and identified by radiological screening. Asymptomatic subjects tended to be younger; median 41 (range 28–66) vs 53 (range 28–66). 15 subjects (83%) had an abnormal CXR; the remainder had abnormalities on HRCT only. PMF was present in 9 cases (50%), one of whom was asymptomatic, and significant emphysema was present in 2 cases (11%). 60% of subjects with simple silicosis had normal spirometry and normal transfer factor (TCO). Seven subjects had obstructive spirometry; four were ex- or current smokers (average 16.5 pack years) and three never smokers. Only three subjects had a restrictive defect on spirometry, two of whom had radiographic evidence of PMF. 81% with a reduction in gas transfer had either a smoking habit or PMF. Lymphopenia was present in six subjects. Ten subjects had immunology performed; four were positive for anti-nuclear antibodies; one subject had a pre-existing diagnosis of systemic sclerosis and one subsequently developed SLE. All subjects had normal renal function. Two subjects developed mycobacterium tuberculosis and two (both smokers) developed bronchogenic carcinoma. Conclusions: Despite the risks of silicosis being well described and legislation aimed at controlling silica exposure local experience suggests a resurgence of silicosis, particularly amongst younger workers who may be asymptomatic and may not have significant lung function changes.